Evaluating the Level of User Loyalty in Library of Tehran University Faculty of Literature and Humanities’s Library Services and Determining their Affecting Factors - Maryam Amini; Mitra Pashootanizade (کتابداری و اطلاع‌رسانی, 2016)
Purpose: The general aim of the present study is to evaluate the level of user loyalty in library of Tehran University Faculty of  Literature and Humanities’s services and to determine their affecting factors. Originality: In Iran, there has been no research on the university library user loyalty measurement with the present study conditions. Findings: Loyalty level in 60/1% of library users in Tehran University Faculty is high, in 39/4% of them is average and in 0/5% of them is low.  "cost of services" and "quality of service" indicators respectively showing (SD =0/87) 4/08 and (SD =0/82) 4/05 were allocated the best score in relation to the factor of “Loyalty level”level . Methodology: This research is descriptive. The study population consisted Faculty of  Literature and Humanities of Tehran University student with  2150 students in bachelor, master and PhD degree. The means of data collection was a questionnaire about evaluation of customer loyalty and its Cronbach's alpha is estimated as 0/7.